Evaluation of the economic burden due to the measles outbreak in the household sector in West Java Province - Maundeng, Agnes Caroline; Kusnanto, Hari; Ahmad, Riris Andono (BKM Public Health and Community Medicine, 2021)
Purpose: Measles remains a significant health issue in Indonesia, particularly in West Java, which experiences a high number and frequency of measles outbreaks. Efforts to control these outbreaks impose a substantial financial burden on households. This study aims to determine the economic burden of the measles outbreak from a household perspective in West Java Province. Methods: This descriptive study used a survey method. Data were collected through interviews with 210 households. The calculation of the economic burden included both direct and indirect costs. Results: The economic burden due to the measles outbreak in East Java Province in 2015 was Rp.92,302,499, including direct costs of Rp.42,282,500 and indirect costs of Rp.50,019,999. The highest economic burden is on households with high education levels, high incomes, and dense living conditions. As many as 39% of households experienced catastrophic financial consequences due to measles. Conclusion: The economic burden of measles in West Java has a significant impact on household economies. The Health Department and community health centers need to make efforts to control measles through increased immunization coverage and enhanced measles surveillance.